DOI: 10.53846/goediss-4548
|View full text |Cite
|
Sign up to set email alerts
|

Essays on Development and Behavior Economics: An Impact Evaluation of the “Bolsa Família” - Conditional Cash Transfer on Education and the Effect of Leadership Identity on Group Cooperation and Elite Capture

Abstract: Chapter 3 42Elite capture and Group Identity: Is Monitoring Effective Against Power Abuse? 423.1 regions. Our results point to a significant increase in Enrollment rates and Attendance among recipients. Furthermore, when different groups and regions are compared, we find that recipients in less developed regions benefited more from program participation than groups in less developed regions, indicating that the program was able to close the gap in education between more and less developed areas.Chapter 2 studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…Several studies have evaluated the effectiveness of such schemes in Latin America, where conditional-cash-transfer schemes have been designed to assist youth labour market integration by extending education and improving young people's skills profile. Impact evaluation studies in Brazil and Mexico found that conditional-cash-transfer programmes significantly raised school attendance in rural areas, while the results in urban areas have been positive but rather modest (Attanasio et al, 2008;Schaffland, 2012). A strengthening of conditional cash transfers can also be used to avoid high dropout rates from education during the economic crisis and help to improve conditions for labour market integration once the crisis is over, as can be illustrated with the case of Costa Rica.…”
Section: Education and Training Policymentioning
confidence: 99%
“…Several studies have evaluated the effectiveness of such schemes in Latin America, where conditional-cash-transfer schemes have been designed to assist youth labour market integration by extending education and improving young people's skills profile. Impact evaluation studies in Brazil and Mexico found that conditional-cash-transfer programmes significantly raised school attendance in rural areas, while the results in urban areas have been positive but rather modest (Attanasio et al, 2008;Schaffland, 2012). A strengthening of conditional cash transfers can also be used to avoid high dropout rates from education during the economic crisis and help to improve conditions for labour market integration once the crisis is over, as can be illustrated with the case of Costa Rica.…”
Section: Education and Training Policymentioning
confidence: 99%